EDUKASI DAN IMPLEMENTASI LITERASI NUMERASI SISWA DI SD NEGERI BELUMBANG KOTA CILEGON - Diyajeng Luluk Karlina; Karlina, Diyajeng Luluk; Mufit, Choirul; Permata, Endi; Kurnianingtyas, Rahajeng (Politeknik Perkeretaapian Indonesia Madiun, 2025)
Literacy and numeracy can be interpreted as basic skills that must be possessed by elementary school students. Elementary school students must have the skills to process information and knowledge that includes text, symbols, numbers, graphs and tables. This provision will be very useful when elementary school students socialize with the community environment. This Community Service aims to provide education to elementary school students about the importance of literacy and numeracy which is carried out through various activities. Order for elementary school students to be interested in this numeracy literacy activity, this activity is packaged in the form of a game. These activities include a reading corner, thematic jellyfish hunting, and a numeracy park. The results of the activities carried out showed an increase in literacy and numeracy, this is evidenced by the increasing post-test scores of elementary school students.